2021
DOI: 10.1002/ijfe.2469
|View full text |Cite
|
Sign up to set email alerts
|

Does the quality of country‐level governance have an impact on corporate environmental disclosure? Evidence fromGulf Cooperation Councilcountries

Abstract: Despite the growth in corporate environmental disclosure (CED) across the world, there remains considerable heterogeneity in the extent to which firms disclose their environmental impacts. To better understand these changes and variations, we identify possible macro-level determinants of CED. Drawing on institutional theory, we examine the influence of country-level governance (CLG) upon CED amongst the non-financial sectors in Gulf Cooperation Council (GCC) countries. Descriptive findings obtained using a cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 125 publications
4
31
0
2
Order By: Relevance
“…There has been a noticeable intensification of environmental disclosures in annual reports in both developed and developing countries (Albitar et al , 2020; Agyei and Yankey, 2019; Belal et al , 2010; Deegan and Gordon, 1996; Gerged et al , 2021b; Kolk, 2004; Jariya, 2015; Mohmed et al , 2019; Salem et al , 2020). For instance, a survey conducted by KPMG with 4100 companies located across 41 countries concluded that 93% of the world's largest 250 companies use their annual reports to reveal the impact of their businesses on environment and society, with noticeable growth in CED across emerging economies (KPMG, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been a noticeable intensification of environmental disclosures in annual reports in both developed and developing countries (Albitar et al , 2020; Agyei and Yankey, 2019; Belal et al , 2010; Deegan and Gordon, 1996; Gerged et al , 2021b; Kolk, 2004; Jariya, 2015; Mohmed et al , 2019; Salem et al , 2020). For instance, a survey conducted by KPMG with 4100 companies located across 41 countries concluded that 93% of the world's largest 250 companies use their annual reports to reveal the impact of their businesses on environment and society, with noticeable growth in CED across emerging economies (KPMG, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, there is compelling evidence to affirm the growth of CED across developed countries (Deegan and Gordon, 1996; Deegan et al , 2002; Campbell, 2004; Hogan and Lodhia, 2011). The growth of CED in developing countries, however, remains limited (Gerged et al , 2018, 2021b; Mahadeo et al , 2011; Amran and Siti-Nabiha, 2009), even amidst concerted efforts by companies in these countries to replicate the disclosure practices of developed countries through the adoption of internationally recognized accounting rules and regulations (Belal, 2001). Belal and Cooper (2011) argue that this is due to firms' reluctance to disclose sensitive or confidential information, specifically those related to environmental responsibilities, coupled with a compelling need to publish brief annual reports that are not conducive to CED.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, scholars have conducted a large body of research on environmental disclosure at the corporate level, including the influencing factors [1,8], the economic consequences [9], environmental performance [10][11][12][13][14][15][16], and regional effects [17,18], while few studies have extended this research to the governmental level. Huang (2017), Gao (2018Gao ( , 2020, Zheng (2018), and Yang (2019) studied the influencing factors of GEID, including the stakeholders (e.g., governments, enterprises, the public, social media, non-governmental environmental organizations, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…First, with the exception of Cohen et al (2002;, the existing studies as discussed above do not investigate the effects of institutional factors, such as the legal and regulatory environment and government intervention, on ACE. Yet, it is suggested that these are important factors of corporate governance effectiveness (e.g., Aguilera and Jackson, 2003;Gerged et al, 2021a;Gerged and Elheddad, 2020;Gerged et al, 2021c). Consistent with this, Cohen et al (2002; find the auditors perceived ACs of nonfinancial firms as powerful and effective in the post-SOX but weak and ineffective in the pre-SOX period.…”
Section: Related Studiesmentioning
confidence: 78%
“…This is particularly so because the degree to which the AC can be effective in its role is affected by factors within the environment in which the firm operates (Mangena and Chamisa, 2008;Baxter, 2010;Ghafran and O'Sullivan, 2013). However, we know very little about ACs in developing countries, particularly in Africa, a continent perceived as risky due to weak investor protection laws (Gerged et al, 2021a;Nuskiya et al, 2021;Klapper and Love, 2004;Mangena and Tauringana, 2007;Waweru et al, 2019).…”
Section: Introductionmentioning
confidence: 99%